Framework for Online Business Transactions Via Instant Messaging Using Natural Language Processing and Business Ontology - Engku Fadzli Hasan, Syed Abdullah; Azrul Amri, Jamal; Rohana, Ismail; Hasni, Hassan; Nur Farah Afifah, Ahmad Sukri (2017)
Instant messaging (IM) has become a popular way to communicate with clients and customers in the business world. IM is a natural way for businesses to provide real-time services to customers. It adds a flexible and comforting human element to an otherwise automated process. Nevertheless, online business activities using IM involve a lot of repetitive and redundant tasks. Current IMs only allow information sharing without any business transactions functionalities. Manually managing business on IM is highly time consuming. At present, there are no framework available for automated online business transactions utilizing IM. The objective of this study is to propose a framework for online business transactions such as product information, inventory, and order process via automated IM called Virtual Assistant (VA). The system uses Natural Language Processing and collected database. A prototype will be developed based on the proposed framework. It is anticipated that the proposed approach will serve as an automated customer service consultant that will enable fast and efficient online business transactions.